MANAJEMEN HUBUNGAN MASYARAKAT DALAM MEMBANGUN CITRA SEKOLAH MODEL PADA ERA DIGITAL DI SMA NEGERI 5 KOTA JAMBI - Utami Putri, Kirana; lestari, Winda; aini, Nur; Novrianto, Muhammad; Iryani, Eva (STKIP Subang, 2026)
This study examines public relations management in building the image of a model school in the digital age at State Senior High School 5 in Jambi City. The study is motivated by the importance of the public relations role in strengthening communication between the school and the community and in building a positive institutional image through digital media. The objective of this study is to analyze the implementation, strategies, and effectiveness of public relations management in enhancing the school’s reputation. This study employs a qualitative descriptive approach with data collection techniques including interviews, observations, and documentation. The research informants consisted of students, teachers, and the Vice Principal for Public Relations. The results of the study indicate that public relations management at State High School 5 in Jambi City has been effective through the use of digital platforms such as Instagram, TikTok, and the school website to publicize various school activities and achievements. Public relations also plays a crucial role in coordinating school programs, establishing partnerships with external agencies, managing public services, and maintaining communication with parents and the community. The implementation of Standard Operating Procedures (SOPs), strategic communication models, and the school’s status as one of the “Model Schools” in Jambi Province further strengthen the school’s positive image and enhance public trust. Overall, public relations management makes a significant contribution to enhancing the school’s reputation and fostering student achievements in the digital age